THE USE OF CHEMOPROPHYLAXIS OR NOT FOR DVT IN SPINE SURGERY: A SYSTEMATIC REVIEW - Cavassin,Bruno Landal (2022)
ABSTRACT Objective: To compare pharmacological and non-pharmacological prophylaxis in elective spine surgery to determine the risks of DVT, PTE, and epidural hematoma (EH) in both groups, as well as their respective treatment effectiveness. Methods: Systematic review and meta-analysis based on systematically searched articles, using combinations of MeSH terms related to chemoprophylaxis and non-chemoprophylaxis for prevention of deep vein thrombosis and pulmonary embolism in elective spine surgery. Adult patients were eligible for inclusion in the study, except for those with trauma, spinal cord injury, neoplasms, or those using vena cava filters. Results: Five studies were selected for this systematic review and meta-analysis: 3 retrospective studies, 1 prospective study, and 1 case series. Data analysis showed that 4.64% of patients treated with chemoprophylaxis had an unfavorable outcome regarding DVT, while this outcome occurred in 1.14% of patients not treated with chemoprophylaxis (p=0.001). Among patients using chemoprophylaxis, only 0.1% developed epidural hematoma and 0.38% developed PTE. Among those on non-pharmaceutical prophylaxis, 0.04% had EH (p=0.11) and 0.42% had PTE (p=0.45). Conclusions: No benefits were found for chemoprophylaxis as compared to non-chemoprophylaxis in preventing DVT in elective spine surgery, nor was there an increased risk of epidural hematoma or fatal thromboembolic events. Level of evidence III; Therapeutic studies; Investigation of treatment results.